Simulation of the Tuna Freezing Process and Evaluation of Factors Influencing the Freezing Time of the Tuna - Huong, Hoang Thi Nam; Hoang, Do Huu; Sim, Vo Van (The Indonesian Institute of Science and Technology Research, 2024)
This paper presents the simulation of the tuna freezing process by using ANSYS software. Based on simulation results, factors affecting the freezing time including air velocity and freezing temperature were determined. Within the air velocity range w = (5÷15) m.s-1, an increase in the velocity by Ñw =1 m.s-1 led to a decrease in the freezing time by Ñt = (7.2÷2.3) %. When the freezing temperature was reduced by Ñte = 1 K, the freezing time was reduced by Ñt = (3.2÷2.5) % in the freezing temperature range te = (–35÷–45) oC.